Da educação especial à educação inclusiva: uma análise dos trabalhos de conclusão do curso de pedagogia da Unisinos (1964-2014) - Heinle, Vivian (Universidade do Vale do Rio dos Sinos, 2016)
This paper describes and analyzes how and where historical and legal conditions the school inclusion issue is addressed in the Faculty of Education of the Universidade do Vale do Rio dos Sinos (Unisinos), from 1964 to 2014, under the final papers. For this project, the research seeks grounding in the theoretical fields of Education and Inclusion and hinges critically with post-structuralist perspective of Michel Foucault. The approach used is constituted by documentary analysis, from the perspective of cultural history, as suggested Grazziotin and Almeida (2012), based on Roger Chartier. The empirical corpus was made from the examination of 3,480 final papers, analyzed over 15 months in the Collection of the University School of Humanities. During this period, we used the theoretical and methodological tools of the fields mentioned to isolate, group and regroup, make relevant and interrelate the amount of information found. This method identified 480 documents that addressed in one way or another, school inclusion, produced over five decades of the Faculty of Education Unisinos. The results of this study allow us to describe and analyze some of the possible conditions that enabled certain forms of knowledge production on school inclusion in a given time and space, in the course of Pedagogy, from two categories. The first category is entitled From Special Education to Inclusive Education: a shift in emphasis and tries to show how, in the first decades analyzed (1964-1989), the terms include school and inclusive education is still not included in the vocabulary of Education and not part of the production of knowledge in Pedagogy. The second category is called Inclusive Education: everyone should be included and addresses historical fragments of inclusive education, especially in Brazil, changing Unisinos curricula and public policies for school inclusion, linked to the chosen TCCs. In addition, when using the Brazilian legal arrangements developed between the decades of 1990-2014, seeks to show how the school inclusion, understood as imperative of Contemporaneity, gained political and educational visibility from the 1990s.
Keywords: Pedagogia; Inclusão escolar; Educação especial; Educação inclusiva; Pós-estruturalismo; História cultural; Pedagogy; School inclusion; Special education; Inclusive education; Post-structuralism; Cultural history; ACCNPQ::Ciências Humanas::Educação